Time for Clean Energy? Cleaner Fuels and Women's Time in Home Production - Farzana Afridi; Sisir Debnath; Taryn Dinkelman; Komal Sareen (Institute of Labor Economics (IZA), 2022)
In much of the developing world, cooking accounts for most of women's time in home production. Does reliance on biomass for cooking drive this time burden? To assess time-savings from shifting towards cleaner fuels, we revisit a clean energy information experiment in rural India. Treatment villages were randomly assigned to receive information about negative health effects of cooking with solid fuels and about public subsidies for cleaner Liquid Petroleum Gas (LPG). Using rich time use data and a propensity score matching approach, we estimate that switching towards cleaner cooking fuels could potentially save 19-20 minutes of home production time per day. Exploiting the randomized information nudge and endline data collected one year after the intervention, our intent-to-treat estimate of actual time saved is 5 minutes per day. We discuss why nudges towards cleaner energy use at home are unlikely to generate transformative shifts in women's home production time.
Keywords: O13; J22; 330; time use; home production; energy use; India